Factors Affecting The Nutrional Status Of Toddlers In Pkm Muara Nasal, Kaur District - Sunarsih, Nani; Sari, Fikitri Marya; Habibie, Julius (Universitas Dehasen Bengkulu, 2022)
: In Indonesia, the problem of nutritional status still needs attention. Based on Riskesdas data, it is known that the prevalence of malnutrition and undernutrition in children under five is 17.7%, while the prevalence of nutritional obesity is 11.8%. The purpose of this study was to determine the factors that influence the nutritional status of children under five in PKM Muara Nasal, Kaur Regency. The method used is a descriptive research design with a cross sectional approach. The population in this study were all mothers who had toddlers in the PKM Muara Nasal Area, Kaur Regency. This study uses the Chi-Square test. The results of the univariate analysis were obtained in the form of the majority of respondents with good nutritional status (82.6%), more than half of the respondents had a high education (57%), almost half of the respondents had good knowledge (41.9%), almost all of the respondents worked (77.9% and more than half of the respondents (64%) had income ≥Rp. 2,387,220. Meanwhile, the bivariate results revealed that there was a relationship between education and the nutritional status of toddlers (p-value: 0.000) , knowledge with under-five nutritional status (p-value: 0.032), work with under-five nutritional status (p-value: 0.014), and income with under-five nutritional status (p-value: 0.008) The combination of education with knowledge and education with work and income will have an impact on mother's behavior related to the nutritional status of toddlers. Therefore, parents should increase their knowledge through both formal and non-formal education, and pay attention to the nutritional content consumed by their toddlers.